Quantitative analysis of performance of a hydrogen peroxide-based glucose biosensor - Abd. Aziz, Azila (Penerbit UTM Press, 2009)
A partial glucose biosensor was constructed using a selective internal layer, an enzyme layer and a gold electrode. Both membrane layers are based on cross-linked polyvinyl alcohol (PVA). The performance of the partial glucose biosensor was analyzed particularly with respect to the interfering effects of acetaminophen, a non-ionic molecule. The sensitivity of the immobilized enzyme to glucose was high but it was not high enough to counter acetaminophen interference. The addition of the moderately selective PVA internal layer did not seem to have a significant effect on interference. A mathematical model was then used to analyze the performance of a completed biosensor. A simulated external layer was added to the two layers. The mathematical model predicted that the addition of an external layer with lowered permeability to solutes could improve the performance of the sensor.